2021
DOI: 10.1007/s15010-021-01633-6
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive ventilation versus mechanical ventilation in hypoxemic patients with COVID-19

Abstract: Purpose Limited mechanical ventilators (MV) during the Coronavirus disease (COVID-19) pandemic have led to the use of non-invasive ventilation (NIV) in hypoxemic patients, which has not been studied well. We aimed to assess the association of NIV versus MV with mortality and morbidity during respiratory intervention among hypoxemic patients admitted with COVID-19. Methods We performed a retrospective multi-center cohort study across 5 hospitals during March-April 2020. Outcomes included mortality, severe COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 27 publications
0
17
0
4
Order By: Relevance
“…After evaluating and assessing as much as 257 potential studies, 201 studies were removed due to outcome of interest being not available. In the end, what underlay this meta-analysis were eligible fifty-six articles with 426,261 COVID-19 patients [5] , [6] , [7] , [8] , [9] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] . The detail of selection process is shown by a chart flow in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…After evaluating and assessing as much as 257 potential studies, 201 studies were removed due to outcome of interest being not available. In the end, what underlay this meta-analysis were eligible fifty-six articles with 426,261 COVID-19 patients [5] , [6] , [7] , [8] , [9] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] . The detail of selection process is shown by a chart flow in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…This emulates observations globally; for instance, a multicenter cohort study across 5 hospitals (March-April 2020) reported that 83% patients of those IMV died, while only 32% in the NIV subset died (unadjusted OR=10, 95% CI 6.7-17). 19 In a case series reported by Chand et al 274 (91.3%) patients received IMV; and 55.8% died, and 26 patients managed with a HFNC had a much lower 30-day mortality (15.4%). 21 In a systematic review and meta-analysis of 10,150 patients across Asia, Europe and North America, Armstrong et al describe a combined ICU mortality of 41.6% (34.0-49.7%), with a reduction over time seen in post-hoc analysis.…”
Section: Aki Acute Kidney Injury Stemi St Elevation Myocardial Infarc...mentioning
confidence: 95%
“…18 Later, in March-April 2020, in an audit on 688 patients, Forrest et al reported that as many as 78% received NIV, while 22% received IMV. 19 And in China, 17.6% (of 239) patients were described to receive IMV, whilst 52.1% received NIV. 20 In our cohort, 64.3% received NIV, and 16.5% were intubated (IMV).…”
Section: Aki Acute Kidney Injury Stemi St Elevation Myocardial Infarc...mentioning
confidence: 99%
“…Although the multivariable regression attempted to address bias inherent in this nonrandomized study, it is not clear whether the higher mortality in this study reflects severity of illness in those intubated or a true cause and effect. 45 In patients with confirmed COVID-19 treated in respiratory units outside the ICU with either HFNO (n 5 163, 24.3%) or CPAP/NIV (n 5 507, 75.7%), the intubation rate was similar in the 2 groups, but the mortality was lower in the HFNO group. 36 In an interim analysis of the international, multicenter HOPE COVID-19 cohort (1933 patients), 390 (20%) patients were treated with NIV, 44.4% of whom had the composite outcome of death or need for intubation.…”
Section: Effectiveness Of High-flow Nasal Oxygen and Noninvasive Vent...mentioning
confidence: 96%